Asociación entre el esquema cognoscitivo y las reacciones conductuales en consumidores de substancias psicoactivas. - Bríñez Horta, José Arturo (Acta Colombiana de Psicología, 1998)
A relationship between cognitive schema and behavioral reaction was studied in consumers and non-consumers of psychoactive substances. To reach this objective, reclassified items of Millón Clinical Multiaxial Inventory - II (MCMI-I1) were applied to a sample 40 polyaddicts and 44 non-consumers. Participants were at least 18 years old, men and women, and residents in Santa Fe de Bogotá. The results revealed significant relationships between misuse and behavioral reactions. Both dysfunctions were also significant more frequently in consumers than in non-consumers (p < 0.001) Results also revealed that there is less probability of error when misuse is predicted from cognitive schema and from behavioral reactions than the opposite way.